2014
DOI: 10.2175/193864714815942116
|View full text |Cite
|
Sign up to set email alerts
|

Mainstream Nitrite-Shunt with Biological Phosphorus Removal at the City of St. Petersburg Southwest WRF

Abstract: The City of St. Petersburg (Florida) Southwest Water Reclamation Facility achieves significant levels of nitrogen (N) and biological phosphorus (P) removal. N removal is via SND from operating the aerated zones at low DO. Despite the low DO operation, very good biological P removal performance is achieved. P removal is sustained at mixed liquor summer temperatures reaching 30°C. Full-scale performance data and detailed bench-scale testing were conducted to assess the N and P removal at low DO. Full-scale resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…In the A2O configuration, TIN removal efficiency was the same, regardless of the amount of SND that occurred. This suggests that process configurations with a preanoxic zone (e.g., MLE or A2O) are less likely to benefit from increased TIN removal by implementing low DO aeration control strategies than configurations without (A/O), and this would appear to be consistent with full‐scale experience elsewhere (Jimenez, Wise, Burger, Du, & Dold, 2014). This should be rationalized with the fact that TIN removal was higher for A2O configuration than A/O configuration (Table 2).…”
Section: Discussionsupporting
confidence: 65%
“…In the A2O configuration, TIN removal efficiency was the same, regardless of the amount of SND that occurred. This suggests that process configurations with a preanoxic zone (e.g., MLE or A2O) are less likely to benefit from increased TIN removal by implementing low DO aeration control strategies than configurations without (A/O), and this would appear to be consistent with full‐scale experience elsewhere (Jimenez, Wise, Burger, Du, & Dold, 2014). This should be rationalized with the fact that TIN removal was higher for A2O configuration than A/O configuration (Table 2).…”
Section: Discussionsupporting
confidence: 65%
“…While conditions for AOB proliferation and NOB suppression are well known for reject water treatment (Hellinga et al, 1998) 2008) while high DO was found to favour AOB over NOB in other mainstream studies (Cao et al, 2013;De Clippeleir et al, 2013;Remgi et al, 2014). Jimenez et al (2014) describes a twostage anaerobic(25%)-aerobic(75%) Phoredox (or A/O) plant (Southwest WWTP in St Petersburg, Florida, USA) treating an influent wastewater with a COD/TKN ratio of 7:1 and temperature between 23 and 30°C at low aerobic reactor DO (0.4 to 0.1 mgO/ℓ). This plant achieves a low effluent total inorganic N (2-4 mgN/ℓ) and low ortho-P (0.1 mgOP/ℓ).…”
Section: Figurementioning
confidence: 99%
“…121 First full-scale references are available in warm weather conditions (i.e. wastewater temperature above 20°C) 123 , and next steps should focus to implement nitritation/denitratation in colder climates.…”
Section: Developing Mainstream Shortcut Nitrogen Removalmentioning
confidence: 99%